Cumulative Incidence of Hypertension by 55 Years of Age in Blacks and Whites: The CARDIA Study. Issue 14 (17th July 2018) - Thomas, S. Justin; Booth, John N.; Dai, Chen; Li, Xuelin; Allen, Norrina; Calhoun, David; Carson, April P.; Gidding, Samuel; Lewis, Cora E.; Shikany, James M.; Shimbo, Daichi; Sidney, Stephen; et al.
Abstract : Background: Blacks have higher blood pressure levels compared with whites beginning in childhood. Few data are available on racial differences in the incidence of hypertension from young adulthood through middle age. Methods and Results: We calculated the cumulative incidence of hypertension from age 18 to 55 years among participants in the CARDIA (Coronary Artery Risk Development in Young Adults) study. Incident hypertension was defined by the first visit with mean systolic blood pressure ≥130 mm Hg, mean diastolic blood pressure ≥80 mm Hg, or self‐reported use of antihypertensive medication. Among 3890 participants without hypertension at baseline (aged 18–30 years), cumulative incidence of hypertension by age 55 years was 75.5%, 75.7%, 54.5%, and 40.0% in black men, black women, white men, and white women, respectively. Among participants with systolic blood pressure/diastolic blood pressure <110 and 70, 110 to 119/70 to 74, and 120 to 129/75 to 79 mm Hg at baseline, blacks were more likely than whites to develop hypertension: multivariable‐adjusted hazard ratios 1.97 (95% confidence interval, 1.65, 2.35), 1.80 (95% confidence interval, 1.52, 2.14), and 1.59 (95% confidence interval, 1.31, 1.93), respectively. Parental history of hypertension and higher body mass index, serum uric acid, and systolic blood pressure/diastolic blood pressure categories were associated with a higher risk for hypertension among blacks and whites. A higher Dietary Approaches to Stop Hypertension diet adherence score was associated with a lower risk for hypertension in blacks and whites. Conclusions: Regardless of blood pressure level in young adulthood, blacks have a substantially higher risk for hypertension compared with whites through 55 years of age.